Spectrum of nonhematological pediatric tumors: A clinicopathologic study of 385 cases - Rajpal Singh Punia; Irneet Mundi; Reetu Kundu; Geetanjali Jindal; Usha Dalal; Harsh Mohan (Indian Journal of Medical and Paediatric Oncology)
Background: The aim of this study is to understand the epidemiology of tumors in children in our region due to a paucity of studies on the histologic review of the childhood tumors in general and benign tumors in particular. Materials and Methods: The records of all the tumors diagnosed histopathologically in children <14 years of age during a period of 8-year (2005-2012) were reviewed. Results: A total of 385 tumors were seen in the age range of 1 month-14 years with 231 (60%) in boys and 154 (40%) in girls. Highest number of cases, 224 (58.18%) were in the age group of 10-14 years. Benign tumors comprised 275 (71.43%) cases while the malignant tumors accounted for 110 (28.57%) cases. In benign tumors, vascular tumors were in majority with 68 cases, while in malignant category bone tumors were most common with 36 cases. Conclusions: Although the exact incidence rate cannot be provided by this hospital-based study, the information is useful in showing patterns of childhood tumors. We included both benign and malignant tumors, while most of the studies in the past have focused mainly on malignant tumors in children.